Analisis Pemikiran Teologi Islam Rasional Sutan Takdir Alisjahbana Menuju Peradaban Modern - Atika Yulanda (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2021)
Humans as religious creatures will always hold their belief in One God. The belief in God is embedded in theological issues. Theology here is a theme related to divine issues, God's relationship with humans, nature and His attributes. Humans are gifted by Allah in the form of reason by which they are able to judge and cultivate what is good and what is right. In addition, with the potential of their intellect, they are also able to prove the existence of God's power and the existence of God in human life. Intellect here does not position it as the highest but is in line with revelation as the source of Islamic teachings. This theology is called rational theology. In rational theology the positions of reason and revelation are parallel. Reason as confirmation and revelation as information. An Indonesian cultural figure who puts his thoughts related to theology, namely Sutan Takdir Alisjahbana. He is of the view that humans with the potential of their intellect are able to compete with the outside world and are able to keep up with the times. However, it is not justified to abandon the values ​​contained in the Qur'an and Hadith. This rational theology of Sutan Takdir Alisjahbana assesses reason as being able to keep up with the times and so that Muslims do not experience setbacks. The setbacks that are happening now are due to those who do not want to be open to the Western world which has been advanced and is only static. Meanwhile, in the teachings of Islam, humans are required to use the potential of reason that has been granted by Allah SWT. This rational Islamic theology is very important for the development of Islam today because there are still human thoughts that are still static and closed to knowledge that comes from outside.